Pelatihan Ladder Drill Ickey Shuffle Dan Side Jump Sprint Terhadap Peningkatan Kecepatan Dan Kelincahan Atlet Kabaddi - Padmawan, I Putu Rega; Wahjoedi, H; Dharmadi, Made Agus; Suratmin, Suratmin; Wijaya, Made Agus (Departemen Kesehatan Dan Rekreasi Fakultas Ilmu Keolahragaan Universitas Negeri Padang, 2024)
There is a decrease in the effectiveness of the game from one of the Badung Regency Kabaddi Teams which previously won the overall champion at the Bali Provincial Sports Week in 2017 and 2019. The purpose of this study was to analyze the effect of Ladder Drill Ickey Shuffle and Side Jump Sprint training on increasing speed and agility in Badung kabaddi athletes. The type of research used is experimental research. The research design to be used is Quasi Experimental Design. The population in this study were all Badung Regency kabaddi athletes totaling 86 people. The sampling technique used is purposive sampling technique. The total research sample used was 48 people consisting of Ladder drill ickey shuffle 16 people, Side jump sprint 16 people, and control 16 people. This research has several data collection methods used, namely the test method and the documentation method. The data analysis technique uses quantitative and qualitative analysis. The results showed that there was a relationship between the type of training Ladder Drill Ickey Shuffle and Side jump sprint to increase speed in Badung Kabaddi Athletes which was shown with a value of 0.003 <0.05 in the experimental group and control group and there was no relationship between the type of training Ladder Drill Ickey Shuffle and Side jump sprint to increase agility in Badung Kabaddi Athletes which was shown with a value of 0.246>0.05 in the experimental group and control group.